2021
DOI: 10.3390/w13152040
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Improved Water Supply Services Based on Asset Management: A Contingent Valuation Study in South Korea

Abstract: The pressure on water infrastructure has increased due to an increase in the number of aging water pipes. Aging pipes are prone to failure, causing significant financial losses and service disruptions. The increasing number of aged pipes and limited budget for pipe rehabilitation or replacement necessitates water infrastructure asset management to ensure sustainable water supply services. In this study, contingent valuation was used to estimate the willingness to pay (WTP) and value improved water supply servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The highest attribute change (61.38%) was observed for the third attribute (involving increasing plantation of other tree species from minimal to more). The findings are in line with a study by Kim et al [ 69 ] which assessed the non-market environmental values of biodiversity conservation in Vietnam and indicated that residents were WTP a monthly payment of VND 913 for a % increase in healthy vegetation.…”
Section: Discussionsupporting
confidence: 91%
“…The highest attribute change (61.38%) was observed for the third attribute (involving increasing plantation of other tree species from minimal to more). The findings are in line with a study by Kim et al [ 69 ] which assessed the non-market environmental values of biodiversity conservation in Vietnam and indicated that residents were WTP a monthly payment of VND 913 for a % increase in healthy vegetation.…”
Section: Discussionsupporting
confidence: 91%
“…Genius et al [32] explore the WTP for implementing municipal enterprises. Kim et al [13] examine the use of asset management, while Jimenez-Redal et al [19] examine the WTP for operations and maintenance services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, evaluating parallel pipeline projects for a better water supply should not be merely based on economic factors, such as costs and bills. Previous studies often utilized survey-based methods, including the contingent valuation method (CVM), to analyze the value of projects imposed by consumers based on their willingness to pay (WTP), using samples collected from the directly affected area [13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between system and asset management in infrastructure is a critical aspect that ensures the efficient and effective management of physical assets [38]. Infrastructure asset management involves the strategic planning, acquisition, operation, maintenance, and disposal of physical assets such as buildings, roads, bridges, and utilities [39]. The correlation between system and asset management in infrastructure is crucial for effective planning, maintenance, and long-term sustainability [40].…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%